EDITORIAL: Análisis de la propuesta de nueva Constitución a la luz de principios del constitucionalismo. - Ovalle Valdés, Alejandra; Cea Egaña, José Luis; Concha Zavala, Germán; Fermandois Vöhringer, Arturo; Romero Guzmán, Juan José; Rosales Rigol, Cecilia; Soto Velasco, Sebastián (Revista Chilena de Derecho, 2022)